Examining English Language Teaching (ELT) Syllabus at Hospitality Program: between the Theory and Practice - Ma’fiyah, Imroatul; Nurkamto, Joko; Gunarhadi; Yusuf, Munawir (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to critically analyse the syllabus’ content as well as identify whether it meets learning objectives or not. The suggestion of remedies will also be given to make learning appropriate and successful. As part of study, twenty English teachers from hospitality program were selected. A qualitative study in terms of document review was administered to critically analyse syllabus components (Brown, 1995; Richards, 2017). In addition, an interview session with a set of five questions based on the prior elements reflecting on the existing syllabus was also conducted with teachers to bring new insights on this study. The analysis of data revealed that the syllabus less appropriate and needs to be re-designed. It should include more activities concerning to the students’ specific needs. Teacher’s perception and experience influences their way of teaching and selecting materials. Teachers’ exploitation on other resources is suggested in order to motivates and push students more.